AN ANALYSIS OF CONSUMERISM IN ORANG KAYA BARU MOVIE: MARXISM THEORY - Jasprit Kaur (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
One of the phenomena that occurs in society is consumerism, in Orang Kaya Baru movie the consumerism behavior is clearly visible, so the researcher can analyze the impact of consumerism and its base and superstructure through Orang Kaya Baru movie use Marxism theory. In Marxism theory itself, it discusses capitalism, class struggle, ideology, and base and  structure which has relation to consumerism, and uses structuralism to interpret the result. The aim of this research is to make people understand more about what consumerism is and aware of its impact, if they are aware then it is beneficial for themselves and the people around them. This research uses qualitative research to describe the phenomenon that occurs. To support the analysis, the researcher uses books, thesis, journals, and Orang Kaya Baru movie as data sources. The result showed that there are 5 base and superstructure and 2 impacts of consumerism. The base and superstructure of consumerism are carried out by the characters, the superstructure is the impact of the base. Then the impact of consumerism in movies is they are never satisfied with what they already have, that is what consumerism does to consumers who cannot control their desires.